Reduced striatal volume in cocaine-dependent patients - GARAVAN, HUGH PATRICK (My University, 2011)
Long-term cocaine consumption is associated with brain structural and functional changes. While the animal literature on cocaine use and dependence has traditionally focused on the striatum, previous human studies using voxel-based morphometry have reported reduced volumes of gray matter in several brain areas, but not in the striatum. Brain magnetic resonance imaging was performed with 20 cocaine-dependent patients and 16 healthy age-, education- and intelligence-matched control men. The cocaine-dependent group had lower gray matter volumes in the striatum and right supramarginal gyrus compared to controls. Within the cocaine-dependent group, years of cocaine use were inversely associated with the volume of the bilateral middle frontal gyrus, left superior frontal gyrus, parahippocampus, posterior cingulate, amygdala, insula, right middle temporal gyrus and cerebellum. These results show that cocaine dependence is associated with reduced gray matter volumes in the target structures of the dopaminergic system. These findings are the first to suggest reduced gray matter in the striatum by means of voxel-based morphometry in human users, thereby linking human results to animal models of addiction. In addition, the relationship between years of use and grey matter volumes in numerous brain regions are consistent with these volume reductions arising as a consequence of the cocaine use.
PUBLISHED
Keywords: Neuroscience; cocaine; addiction